Beispiel Nr: 20
$ \text{Gegeben:} ax^{3}+bx^{2}+cx+d=0 \\ \text{Gesucht:} \\ \text{Lösung der Gleichung} \\ \\ \\ \textbf{Gegeben:} \\ -6\frac{3}{4}x^3-13\frac{1}{2}x^2 =0\\ \\ \textbf{Rechnung:} \\ x^2(-6\frac{3}{4}x-13\frac{1}{2})=0 \Rightarrow x=0 \quad \vee \quad-6\frac{3}{4}x-13\frac{1}{2}=0\\ -6\frac{3}{4} x-13\frac{1}{2} =0 \qquad /+13\frac{1}{2} \\ -6\frac{3}{4} x= 13\frac{1}{2} \qquad /:\left(-6\frac{3}{4}\right) \\ x=\displaystyle\frac{13\frac{1}{2}}{-6\frac{3}{4}}\\ x=-2 \\ \underline{x_1=-2; \quad1\text{-fache Nullstelle}} \\\underline{x_2=0; \quad2\text{-fache Nullstelle}} \\$